Martin Cockburn papers - Cockburn, Martin
Ledger and daybook of Cockburn's household finances and business transactions in Fairfax, Fauquier, King George, Loudoun, and Prince William counties, and the island of Jamaica. Also includes transcripts (1769) of the registry of Truro Parish relating to Pohick Church.
Microfilm edition available
Landowner, businessman, and merchant.
Collection material in English.
Keywords: Pohick Church (Lorton, Va.); Truro Parish (Fairfax County, Va.); Business records -- Virginia -- Fairfax County; Business records -- Virginia -- Fauquier County; Business records -- Virginia -- King George County; Business records -- Virginia -- Loudoun County; Business records -- Virginia -- Prince William County; Business records -- Virginia -- Springfield; Business records -- Jamaica; Merchants -- Virginia; Episcopal Church -- Virginia; Businessmen; Landowners; Merchants